The shape of Herodotean rhetoric : a study of the speeches in Herodotus' Histories with special attention to books 5-9 - Zali, Vasiliki. (International Studies in the History of Rhetoric, 2014)
In The Shape of Herodotean Rhetoric , Vasiliki Zali offers a fresh assessment of Herodotus' rhetorical awareness. Redressing the usual view that considers Thucydides as a significant jump from earlier authors in the rhetorical tradition, Zali attempts to find a place for Herodotus. The volume explores the direct and indirect speeches in Herodotus' fifth to ninth books, focusing in particular on the ways in which they highlight two major narrative themes: the fragility of Greek unity and the problematic Greco-Persian polarity. Through discussion of case studies and Herodotus' literary background, Zali brings Herodotus' sophisticated rhetorical system to life, examines the ways in which this system affects Herodotus' authority, and demonstrates that Herodotus occupies a crucial place in the development of rhetoric.